Microplots and food security: Encouraging replication studies of policy relevant research - Benjamin Douglas Kuflick Wood; Maria Vasquez (Economics: The Open-Access, Open-Assessment E-Journal, 2018)
Replication research is a valuable, yet often misunderstood, tool for increasing our understanding of promising research findings. In this short paper the authors discuss their principles for conducting replication research, explain how they chose a candidate study for replication, describe their replication analysis robustness checks, and give an overview of their approach to interpreting replication results. They also describe some of their lessons learned after working in replication research for over six years.
Keywords: Q18; O13; 330; replication; food security; research transparency; impact evaluation